The Sand Removal Performance and Erosion Characteristics of Shale Gas Wellhead Desander - Jian Zhang; Chang Liu; Dong Lin; Jian Gao; Changchao Qi; Jun Jiang; Bo Kou; Shanbi Peng (Tehnički Vjesnik, 2023)
In the process of shale gas extraction, fracturing technology is often used, and the extracted gas contains large amounts of sand, resulting in the risk of blockage and erosion of surface gathering equipment, which seriously affects safe production. To address this problem, this paper presents a numerical study of the sand removal performance and erosion characteristics of the filter desander used in Sichuan shale gas fields under different operating conditions (flow velocity, sand mass flow rate, operating pressure, and sand particle size) using CFD method. The results show that the increase of shale gas velocity is not conducive to the efficient operation of the filter desander. So the flow velocity should be controlled within 10 m/s as much as possible to avoid the rapid drawdown of separation efficiency and overly high erosion rate. When the sand size increases from 10μm to 100μm, the erosion area of the filter desander changes to sheet-like distribution, and the separation efficiency increases to 85%, a 2.3-fold increase. In addition, the change in operating pressure has a relatively small impact on the erosion wear of the desander.